2022
DOI: 10.3390/buildings12091327
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Investigation of Office Layout Influences on Occupant Satisfaction from Priori and Posteriori Perspectives

Abstract: The layout of an office significantly affects human health, well-being and productivity in multi-occupancy offices, while the relationship and prioritization of various office layout factors have not been clarified. This study conducts a thorough investigation of office layout factors on occupant satisfaction. Existing pieces of literature were deconstructed and reorganized to extract five office layout factors. For a comparative investigation, an analytic hierarchy process-based online survey and a post-occup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 77 publications
0
1
0
Order By: Relevance
“…Moreover, the workplace design positively affected three aspects of culture, especially equality, openness, and collectivity [23,24]. Another study found a significant and positive association between office layout features and organizational culture ratings, which mediate the relationship between the office layout features and job satisfaction [25,26]. In addition, physical environments in offices are associated with recruitment, retention, and productivity of the organization [27].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the workplace design positively affected three aspects of culture, especially equality, openness, and collectivity [23,24]. Another study found a significant and positive association between office layout features and organizational culture ratings, which mediate the relationship between the office layout features and job satisfaction [25,26]. In addition, physical environments in offices are associated with recruitment, retention, and productivity of the organization [27].…”
Section: Introductionmentioning
confidence: 99%